1975
DOI: 10.1104/pp.56.2.300
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Secretion of Maize Root Cap Slime

Abstract: The secreted slime from root cap cells of corn (Zea mays, cv. SX-17) was studied. Production of slime by excised root tips is stimulated by the addition of 40 mM sucrose or fucose and half-strength Hoagland's solution to the incubation medium.Secreted slime was recovered from aqueous solution by precipitation with ethanol. The polymer has a molecular weight greater than 2 X 10-8 daltons and a density of 1.63 g cm-'. Protein is not present in material purified by density gradient centrifugation with cesium chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The polysaccharide produced by roots of corn contains a high proportion of fucose and galactose, together comprising 69% of the neutral sugars of the polymer (9). Using glucoser4C], Harris and Northcote (3) showed that when the distribution of label appearing in fucose was expressed as a ratio of label in xylose, the ratio was higher in the apical 0.5-mm section of the root.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The polysaccharide produced by roots of corn contains a high proportion of fucose and galactose, together comprising 69% of the neutral sugars of the polymer (9). Using glucoser4C], Harris and Northcote (3) showed that when the distribution of label appearing in fucose was expressed as a ratio of label in xylose, the ratio was higher in the apical 0.5-mm section of the root.…”
mentioning
confidence: 99%
“…Using glucoser4C], Harris and Northcote (3) showed that when the distribution of label appearing in fucose was expressed as a ratio of label in xylose, the ratio was higher in the apical 0.5-mm section of the root. An autoradiographic study by Kirby and Roberts (7) 20 ,ug/ml of chloramphenicol, and 5 ,ug/ml of streptomycin (9). For Figure 1.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Their observations were verified and expanded by subsequent workers. The slime from corn was characterized as a high mol wt heteropolysaccharide rich in fucose and galactose (9,17). Secretion and synthesis of slime were studied with high resolution autoradiography (16,19) and by localization of fucose-containing polymers in subcellular fractions from roots incubated in [14CJglucose (2)(3)(4) or [3Hlfucose (20).…”
Section: Introductionmentioning
confidence: 99%